Analisis Bahan Ajar Berbasis Media Gambar untuk Meningkatkan Kemampuan Membaca Siswa Kelas III Mata Pelajaran Bahasa Indonesia di MI Birrul Walidain NW 2 Rensing - Susanti, Yuliana (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
One of the best role models for encouraging kids to learn is visual media, which may be utilized to accomplish educational objectives. Teachers can increase students' interest in the lecture by using image media, which can help with comprehension and memory consolidation. This study aimed to ascertain the type of instructional materials utilized in Indonesian language courses and if image media instructional materials may enhance reading proficiency in Indonesian language courses in class III MI. Rensing of Birrul Walidain NW. Data for the qualitative descriptive study design was gathered through documentation, interviews, and observation. Four steps encompass the data analysis process: gathering data, reducing data, presenting data, and making conclusions. The study's findings demonstrate: Two types of visual aids frequently utilized in Indonesian language courses are 1) visual aids in the form of posters and 2) visual aids in the form of serial photos. Regarding media image, there are four ways that it may help with reading comprehension in Indonesian language courses: a) media usage; b) learning media; c) student reading abilities; and d) teacher training and improvement of student reading skills.